Cadmium Induced Changes in Lipid Peroxidation andAntioxidant Status in Brain of Ovariectomized Rats - Hatungil, Rezan; Yalin, Serap; Comelekoglu, Ulku; Bagis, Selda; Ozlen Sahin, N.; Arslan, Hakan; Eroglu, Pelin; Berkoz, Mehmet (Asian Journal of Chemistry, 2010)
The study was designed to estimate the influence of chronic cadmium administration on lipid peroxidation and antioxidant enzymes in brain tissues of ovariectomized female rats. Rats were divided into four groups as follows: control group, ovariectomy group (Ovx group), cadmium group (Cd group) and ovariectomy- cadmium group (Ovx-Cd group). Twelve weeks after the ovariectomy, isotonic cadmium chloride solution was administered to cadmium and ovariectomy-cadmium group rats as intraperitoneal injection of 0.5 mg/kg three times a week for 18 weeks. The levels of malondialdehyde and superoxide dismutase activity showed a significant increase in the Cd and Ovx-Cd groups and a decrease in the Ovx group when compared to the control group. Catalase activity decreased in the Cd group while no change was observed in the Ovx and Ovx-Cd groups in comparison to the control group. The results of the present study may suggest that chronic Cd administration induces oxidative stress in the ovariectomized rat brain as evidenced by the increasing lipid peroxidation upon alteration in the antioxidant status of the brain tissue.